ANALISA HASIL PEMBANGUNAN MCK PLUS BERBASIS MASYARAKAT DI PROVINSI ACEH - Nur Mutia; Eldina Fatimah; Suhendrayatna Suhendrayatna (Prodi Magister Teknik Sipil Unsyiah, 2018)
Implementation of development of community-based sanitation infrastructure management is a new thing for the people of Aceh, especially the community in the location of community sanitation facilities will be built. Currently more than 90 percent of Acehnese people use individual waste water systems or toilets that have not been properly managed and have not equipped septic tanks so that the sludge is discharged directly into the water body. This condition leads to the spread of disease (epidemic). Septic tanks are rarely aspirated so that it becomes a successor of wastewater that then seep in the soil and contaminate it. This is the reason for the entry of Community sanitation program into a solution in the provision of infrastructure and waste water facilities using Lavatory Plus. The Community sanitation program aims to improve the quality of the environment by increasing access to community-based sanitation facilities. This study aims to identify the results of community-based Lavatory Plus development in terms of management, institutional and financing. Knowing the level of satisfaction and public interest towards community-based Lavatory Plus development. This research will be conducted in 4 (four) regencies / cities with the lowest coverage of sanitation in Aceh Province, Kab. Pidie Jaya, Kab. Aceh Tamiang, Kab. Aceh Barat Daya and Kota Subulussalam by using quantitative methods supported by qualitative analysis. Qualitative analysis was conducted to look at management, institutional and financing aspects. Data collection were taken through observation and interview on the Work Unit of Environmental Sanitation System Development of Aceh Province and District Public Works Office. Data analysis was done by using SWOT analysis and its analysis tool USG (Urgency, Seriousness, and Growth) and performed data processing through Biplot Method with Mini Tab software. SWOT analysis results show the success rate of Community sanitation program management is in quadrant I. The results of analysis of the level of satisfaction and public interest by using Biplot Method assisted software Mini Tab. The level of community satisfaction is 3.63 and the level of public interest is 4.4 ie the average community feels important to the management of the Community sanitation program.